2014
DOI: 10.1016/j.radonc.2014.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy for the prophylaxis of heterotopic ossification: A systematic review and meta-analysis of published data

Abstract: Decreases in rates of HTO over time in this patient population may be a function of more efficacious surgical regimens and prophylactic radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 60 publications
1
57
1
3
Order By: Relevance
“…We therefore chose 10-week followup as a minimum for inclusion. One recent study has shown that HO does not progress beyond 6 weeks [20], and another meta-analysis has shown that 89% of HO is present by 3 weeks and 100% by 8 weeks [19]. In a review of 508 patients treated by a single surgeon, only two of 508 (0.4%) patients had progression in Brooker HO class from 6 weeks postoperative radiographs to final followup [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We therefore chose 10-week followup as a minimum for inclusion. One recent study has shown that HO does not progress beyond 6 weeks [20], and another meta-analysis has shown that 89% of HO is present by 3 weeks and 100% by 8 weeks [19]. In a review of 508 patients treated by a single surgeon, only two of 508 (0.4%) patients had progression in Brooker HO class from 6 weeks postoperative radiographs to final followup [10].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with fewer than 10 weeks followup (n = 12) were excluded, because several studies [10,19,20] suggest that most HO that develops is visible by that point in time. Three of 27 patients in the radiotherapy and débridement group were excluded for insufficient followup and nine of 31 patients in the débridement-only group were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, NSAID administration carries the risk of gastric irritation, occasionally preventing (20-37%) patients from completing treatment [14]. Single dose radiotherapy is widely used and there is persuasive clinical evidence demonstrating its effectiveness as a HO prophylactic following surgery [15][16][17]. Furthermore, radiotherapy and NSAIDs may be given in combination pre-or post-operatively for high-risk patients [18].…”
Section: Clinical Problemsmentioning
confidence: 99%
“…Ectopic ossification is a complex process characterized by the formation of ectopic bone or the deposition of calcium phosphate complexes within muscles, connective tissue, or nerves in aberrant locations (1)(2)(3)(4). The ossification processes may be caused by heredity, surgical intervention or trauma (2,3).…”
Section: Introductionmentioning
confidence: 99%